Correlated choice - Christopher P. Chambers; Yusufcan Masatlioglu; Christopher Turansick (Theoretical Economics, 2024)
We study random joint choice rules, allowing for interdependence of choice across agents. These capture random choice by multiple agents, or a single agent across goods or time periods. Of interest are random joint choice rules which have well defined marginal random choice rules.% as this is necessary for choices to be separable over each dimension. Our interest is in separable choice rules, where each agent can be thought of as acting independently of the other. A random joint choice rule satisfies marginality if for every individual choice set, we can determine the individual's choice probabilities over alternatives independently of the other individual's choice set. We offer two characterizations of random joint choice rules satisfying marginality in terms of separable choice rules. While marginality is a necessary condition for separability, we show that it fails to be sufficient. We provide an additional condition on the marginal choice rules which, along with marginality, is sufficient for separability.
Keywords: D01; D91; 330; Random utility; Correlation; Stochastic choice; Dynamic choice